2020
DOI: 10.1007/jhep11(2020)094
|View full text |Cite
|
Sign up to set email alerts
|

Leptoquarks in oblique corrections and Higgs signal strength: status and prospects

Abstract: Leptoquarks (LQs) are predicted within Grand Unified Theories and are well motivated by the current flavor anomalies. In this article we investigate the impact of scalar LQs on Higgs decays and oblique corrections as complementary observables in the search for them. Taking into account all five LQ representations under the Standard Model gauge group and including the most general mixing among them, we calculate the effects in h → γγ, h → gg, h → Zγ and the Peskin-Takeuchi parameters S, T and U. We find that th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(22 citation statements)
references
References 140 publications
(105 reference statements)
0
22
0
Order By: Relevance
“…In the second we switch on also some of the S 1 couplings to right-handed fermions, and aim to provide a combined explanation for all three anomalies. Finally, we study the limits on the leptoquark potential couplings to the Higgs, which is an analysis largely independent on the couplings to fermions and requires to consider different observables than those studied in the main fit, see also [57]. In any given model there is, of course, no particular reason to expect the exact flavor structures implied by table 4.…”
Section: Scenarios and Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the second we switch on also some of the S 1 couplings to right-handed fermions, and aim to provide a combined explanation for all three anomalies. Finally, we study the limits on the leptoquark potential couplings to the Higgs, which is an analysis largely independent on the couplings to fermions and requires to consider different observables than those studied in the main fit, see also [57]. In any given model there is, of course, no particular reason to expect the exact flavor structures implied by table 4.…”
Section: Scenarios and Resultsmentioning
confidence: 99%
“…More recently, one-loop computations of several observables in this model have been published [54][55][56][57]. The approach adopted in these works is to compute directly in the model the dominant one-loop contributions to the desired observables.…”
Section: Jhep01(2021)138mentioning
confidence: 99%
See 1 more Smart Citation
“…Ref. [457] examined the Higgs decays h → γγ, h → gg and h → Zγ, and showed that the scalar leptoquarks contributions to these can generally be measured with increased precision at the ILC, CLIC, CEPC, FCC-ee and FCC-hh. They also showed that the value of the electroweak oblique observables, S and T (but not U ), can change due to leading order contributions from scalar leptoquarks.…”
Section: Jhep09(2021)080mentioning
confidence: 99%
“…Leptoquarks have been also considered in connection with the phenomenology of the Higgs boson in refs. [5][6][7][8]. It is well known that within the SM and in the present experiments, the multiple Higgs production process is the only way to access the interactions provided by the potential responsible for the spontaneous breaking of the Electroweak (EW) gauge symmetry.…”
Section: Introductionmentioning
confidence: 99%